Wax Scale on Southern Highbush Blueberries in Florida - Oscar Liburd; Doug Phillips (EDIS)
Florida wax scale, Ceroplastes floridensis, is an insect pest causing damage on plants throughout much of the United States, including Florida, where it can be found infesting southern highbush blueberries. This publication is intended to inform Florida blueberry growers about this pest and to discuss management and control alternatives.